Performance of MGNREGS - Aquaculture Convergence: A Study in Tripura, India - Ijardar, R. S.; Sarkar, A.; Upadhyay, A. D.; Biswas, P.; Singh, Y. J. (International Journal of Bio-resource and Stress Management, 2017)
The paper is based on a study conducted in northeastern state of Tripura (India) to comprehend intra-state level performance of work execution relating to excavation and reclamation of ponds under MGNREGS during 2012–13 to 2016–17; and to examine the performance of those built up aquatic resources during post work execution phase. At first phase, analysis of secondary data revealed that the state had executed 82628 nos. of works combining both pond excavation and reclamation jobs during the period under study, of which the share of works on excavation of new ponds and reclamation of existing ones was 65.26% and 34.74% respectively. Signifying possible influence of MGNREGS through such works, while the area under culture fisheries in Tripura registered 7.11% gain during the period, in case of fish production from culture fisheries 18.02% gain was recorded. At the second phase, examination of the performance of post work execution period through a case study conducted in West Tripura district over 65 nos. of MGNREGS beneficiaries, however, revealed that although 81.54% of them had no previous experience of culture fisheries as they became first ever owners of pond, there remained extreme inadequacy in pertaining enabling skill training to them to pursue scientific aquaculture. And that had led to their very poor extent of adoption (29.57%) of scientific aquaculture practices to, in turn, poor accrual of annual fish productivity (735.58 kg ha-1) by them that lagged by 3.3 times from the state average and 3.6 times from the average of West Tripura district, where the study was conducted.